Digitalisasi dalam Kurikulum Pendidikan Agama Islam: Telaah Kontekstual terhadap Dinamika Sosial dan Pendidikan di Indonesia - Viva Khoirun Amala; Chusnul Chotimah; Imam Junaris (Jurnal Teologi Islam, 2025)
The development of digital technology has had a significant impact on the world of education, including Islamic Religious Education (PAI). The PAI curriculum is required to transform in order to remain relevant to the needs of students in the digital era and in line with the ever-changing social dynamics. This study aims to examine how digitalization is integrated into the PAI curriculum and its implications for strengthening character, mastering 21st-century competencies, and increasing learning effectiveness. The method used is a qualitative approach with library research, which analyzes curriculum documents, previous research results, and relevant scientific literature. The results of the study show that the digitalization of the PAI curriculum can enrich learning strategies through the use of digital media, encourage student-centered learning, and strengthen Islamic values ​​through contextual and collaborative approaches. However, this process also faces challenges such as low digital literacy of teachers, potential media misuse, and infrastructure gaps. Therefore, the development of an adaptive PAI curriculum for the digital era requires an active role from all stakeholders, so that religious education remains meaningful, relevant, and contributive in forming a generation that is faithful, knowledgeable, and has noble character.